Rol de las células NK en el desarrollo de la respuesta inmune adaptativa mediada por LT CD8 contra antígenos tumorales - Raffo Iraolagoitia, Ximena Lucía (2016)
Despite the classical function of NK cells in the elimination of tumors, evidence for a regulatory role for NK cells has been emerging in different models. However, this role has not been fully explored in the context of a growing tumor. In this thesis work, we show that NK cells can limit spontaneous cross-priming of tumor antigen-specific CD8 T cells, leading to reduced memory responses. After challenge with MC57.SIY cells, NK cell-depleted mice exhibited a higher frequency of SIY-specific CD8 T cells, with enhanced effector functions. Depletion of NK cells resulted in a CD8 T cell population skewed towards an effector-memory T phenotype which was associated with enhanced recall responses and delayed tumor growth after a secondary tumor challenge with B16.SIY cells. Mechanistically, we found that tumor-primed NK cells displayed an up-regulated expression of the inhibitory molecule PD-L1 and, through interaction with PD-1 expressed on DC, limited DC activation, explaining their reduced ability to induce tumor-specific CD8 T cell priming. Our results suggest that NK cells can, in certain contexts, have an inhibitory effect on anti-tumor immunity, a finding with implications for immunotherapy in the clinic.